Surgical aortic valve replacement in patients aged 50–69 years—insights from the German Aortic Valve Registry (GARY). (14th May 2022) - Vogt, Ferdinand; Santarpino, Giuseppe; Fujita, Buntaro; Frerker, Christian; Bauer, Timm; Beckmann, Andreas; Bekeredjian, Raffi; Bleiziffer, Sabine; Möllmann, Helge; Walther, Thomas; Beyersdorf, Friedhelm; Hamm, Christian; et al.
Abstract: OBJECTIVES: The aim of this study was to analyse the outcome of patients between 50 and 69 years of age undergoing biological or mechanical aortic valve replacement. METHODS: Data were collected from the German Aortic Valve Registry. Data were analysed regarding baseline characteristics and outcome parameters such as 5-year survival, stroke and reintervention. RESULTS: In total, : 3046 patients undergoing isolated surgical aortic valve replacement between 2011 and 2012 were investigated and a propensity score matching was performed. Within this period, 2239 patients received a biological prostheses, while 807 patients received a mechanical prosthesis. Mean age in the biological group was 63.07 (±5.11) and 57.34 (±4.67) in the mechanical group (standardized mean difference 1.172). In the overall cohort, there were more female patients in the biological group (32.7% vs 28.4%) and log EuroSCORE I was higher (5.41% vs 4.26%). After propensity matching (610 pairs), there was no difference in the mortality at 5-year follow-up (12.1% biological vs 9.2% mechanical P = 0.05) nor for reoperation/reintervention (2.5% biological vs 2.0% mechanical, P = 0.546). Patients undergoing mechanical aortic valve replacement suffered from a higher stroke rate 3.3% vs 1.5% ( P = 0.04) at 5-year follow-up. CONCLUSIONS: Aortic valve replacement with biological or mechanical prostheses showed similar 5-year outcomes for survival and reoperation in a propensity-matched cohort, but significantly increased stroke rate after mechanical aortic valve replacement. This could influence the choice of a mechanical valve in younger patients. Abstract : Aortic valve disease is the most frequent heart valve disease in western countries [1].